Roxane Gay’s An Untamed State: A Caribbean Rhizomatic Novel Reflecting the New Transmodern Paradigm - Roldan-Sevillano, Laura (Complutense Journal of English Studies, 2021)
This article explores Haitian American writer Roxane Gay’s An Untamed State (2014) as a novel that represents our intricate and rhizomatic transmodern era. In order to prove this contention, it focuses on the novel’s amalgamation of different literary genres and modes from previous cultural paradigms—namely, the postmodern fairy-tale retelling and the social realist novel—with Euro-American as well as Haitian/Caribbean literary and sociocultural elements. The result of this mélange is a complex narrative of multiple interconnections that offers a nuanced portrait of new millennium Haitian diasporas and locals, and that most especially, recuperates subaltern Haitian voices so as to denounce the “untamed state” of the country. The article concludes by arguing that Gay’s hybrid and relational text effaces an either/or episteme which, although considerably used in Western and postcolonial theories for a while, has now become obsolete and inoperative in such a globalised and entangled world.